Mentorship in Developing Micro Enterpreneur of Rengginang Business in Babakan Mulya Village, Kuningan City, West Java - Yohanes Berenika Kadarusman; Aninda Azaria Hapsari; Rafael Leonardo Marcello; Luthfi Andri; Mikha Irianto; Muhammad Sejati (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
Besides working as a farmer, Mrs. Sutinah has run a business selling rengginang (a form of traditional rice cakes, popular as snacks and crisps as a side dish for main meals) since 2012. Mrs. Sutinah can be said to be the pioneer in the rengginang business around her village, Babakan Mulya, in the city of Kuningan, West Java. Nevertheless, in recent years, Mrs. Sutinah has been facing some challenges due to the emergence of competitors who offer a lower price than that of Mrs. Sutinah’s rengginang. This condition demotivates Mrs. Sutinah from developing her business because many people in the Babakan Mulya village prefer cheap rengginang, regardless of its quality. The purpose of this activity is to help develop Mrs. Sutinah’s rengginang business through three stages: pre-business mentoring, businessmentoring, and post-business mentoring. In the first stage of pre-mentorship, the community service team conducted interviews and field observations to identify the problems faced by Mrs. Sutinah’s business. The second stage involves direct mentorship given to Mrs. Sutinah, who can learn by directly implementing the concepts taught by the team to increase the competitive advantage of her products. In the final stage of post-mentorship, the team monitors and evaluates the success of the business and the actual implementation of the lessons given to Mrs. Sutinah. The pre-mentorship was conducted in one week, followed by the mentor’s accompaniment completed in four weeks. Meanwhile, monitoring and evaluation of Mrs. Sutinah’s engagement and implementation of the gained knowledge and skills were conducted periodically in the next four months after the mentorship ended. The outcomes revealed that the development and sustainability of micro entrepreneur need intensive mentorship, particularly by involving academia to ensure that the knowledge and skill transfer would be effective and consistently implement what they have learned